Hearing the voice of the family: narratives about suffering and spirituality - Margareth Angelo (O Mundo da Saúde, 2010)
The aim of this study was to understand how families of children with cancer express and experience the spiritual dimension of their suffering. Using a narrative research approach, data were obtained by audio recording interviews with 10 Brazilian families of children with cancer. The process of analysis of the narratives generated categories that allow us to connect each family story to others: (1) suffering in cancer situation is an intense personal experience, grounded in universal as well as cultural, family and personal meanings, (2) suffering in cancer places the family in the border of life generating the need to relate to Divine, (3) spirituality is present in the way the family perceive the meaning of the events, (4)spiritual practices area related to searching for meaning of the suffering and to finding answers to existential questions about cancer in family life, (5) suffering generates in the family the need to show and to legitimate the lived pain through narrative. This study on family narrative allow us to understand the illness experience as well as the suffering, as a creative and dynamic process of the individual experience, interactionally constructed which represents the expression of the experience being constructed in the social interactions and sharing meanings of the events.